Kajian Penggunaan Ruang dan Kesehatan Lingkungan Suku Saga di Kabupaten Ende - Setyabudi, Irawan; Ngama, Kristoforus Wasa; Hastutiningtyas, Wahidyanti Rahayu (RUAS, 2020)
Saga Village, Ende Regency, East Nusa Tenggara has a traditional house that becomes its identity, namely Sa’o. Unlike ordinary traditional houses, Sa’o has a customary leader in each house. Thus, the house is not just a place to live but also shows the social hierarchy. Visually, the floor plan is a square with a very steep roof angle so that the roof is visible. The philosophy follows the analogy of the human body, that is, lewu (pedestal/ foot), one (wall/ body), gara (roof/ head). On the macro scale, the Saga settlement pattern follows the contour pattern. There are about 20 houses with the same typology. The use of space in cultural activities is not yet identified. Besides, the position of the contoured landscape without shade and surrounded by forests has a vulnerability to several diseases. The link between space use and environmental health also has not yet been explained. Continuing from previous research on space cosmology, the micro aspect in this study deals with the physical identification of traditional houses. In contrast, in the macro aspect, it discusses the use of space for cultural activities and aspects of environmental health. The data collection was carried out through focus group discussions (FGD) and analyzed using a descriptive qualitative method with an ethnographic approach. The results of this study are descriptions of spaces used for cultural activities at a particular time and place as well as efforts to improve public environmental health. In conclusion, Saga people have local wisdom in terms of traditional architecture, in addition to the intangible form of inherited traditions and efforts to improve environmental health.